ANALISIS PERILAKU KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL DALAM PENYELENGGARAAN PEMERINTAHAN DESA - Hasymi Rinaldi; Mahendra Jaya; Januardi M. Diah (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2018)
ABSTRACT Rapid development of information technology and increased authority of village by the law No. 06 of 2014 on Village, need the existence of transformational leadership. Village head is expected to have ability to respond the changes, and influence the changes to support village development. The purpose of research are identify the ability of village head to respond the change, and identify behavior of transformational and transactional of village head to govern the village government in Kuburaya Regency. Samples of the research are two villages with different characteristics and resources. The two villages are Telukempening and Sungairaya Dalam. The result shows that limitation and lack of resources in Telukempening encourage the village head to be transformational leader, meanwhile village head of Sungairaya Dalam shows the behavior of transactional leadership. Keywords: transformational leadership, transactional leadership, village, information technology